Detection of porcine circovirus 2, porcine parvovirus 1, and torque teno sus virus k2a in wild boars from northeastern Patagonia, Argentina - Iglesias, Néstor Gabriel (Springer, 2023)
Wild boars can act as a reservoir of pathogenic viruses that affect the pig industry. Here, we assessed the presence of porcine circovirus 2, porcine parvovirus 1, and torque teno sus virus k2a in wild boars in northeastern Patagonia (Argentina). Total DNA was extracted from the tonsils of 27 animals (collected between early 2016 and mid-2019) and used to prepare sample pools, which were subjected to viral detection through two-round PCR assays. Sequencing of the amplification products and phylogenetic analysis confirmed the occurrence of all of the aforementioned infectious agents.
Keywords: Ciencias naturales::Ciencias biológicas